(untitled) (Research, Society and Development, 2020)
The problematization of the article refers to the analysis of the possibility of relativizing the principle of impartiality by the Judiciary. Therefore, it is necessary to approach the evidence system, with a brief concept and definitions, as well as to discuss the inversion of the burden of proof and the magistrate’s instructive power. Due to the problematization, observance of procedural principles is also required, emphasizing the principle of impartiality and the principle of cooperation. Finally, it is intended to conceptualize the real truth by the judge. Therefore, a deductive research based on doctrine and legislation makes up the appropriate argumentative framework.